Analysis of Low-Stiffness-Resilient-Shaft (LSRS) for Semi-Active-Steering (SAS) System - HUSSAIN, NAJAF (2016)
The use of the Low-Stiffness-Resilient-Shaft (LSRS) in the Semi-Active-Steering (SAS) system helps remove the drawbacks of the conventional and Steer-By-Wire (SBW) systems. According to previous research on the LSRS, a torsional stiffness range of 5 to 15 N.m.rad-1 was determined to be ideal. However, the underlying structure of the LSRS was not finalized. This also meant that the effect of changing structural properties of the LSRS on its torsional behavior was unknown as well. Wire ropes along with bearings were used as the structural members of the LSRS. Study was conducted on a right lay single strand wire rope and it was found out that due to its lay structure, there was a percentage difference of 10.33% between its clockwise and anti-clockwise torsional stiffness. To achieve equal torsional stiffness, a configuration namely Variation 2 was shortlisted as the base layout of the LSRS, as it had similar torsional stiffness in both directions. Furthermore, the effect of changing structural properties of the LSRS on its torsional behavior were also studied. It was found out that the torsional stiffness of the LSRS decreased with the increase in total length, with the highest torsional stiffness of 4.59 N.m.rad-1 from a length of 100 mm. Similar results were observed with the increase in pitch values of the wire ropes, albeit the change was not significant. The increase in the wire diameter caused an increase in torsional stiffness with the highest calculated torsional stiffness of 2105.26 N.m.rad-1 from a wire diameter of 6 mm. It was also noted that an increase in the angle of bend caused an increase in the torsional stiffness as well. A torsional stiffness of 7.16 N.m.rad-1 was calculated for an LSRS with a bend angle of 105o. Furthermore, it was also observed that the increase in the number of bearings also caused an increase in the overall torsional stiffness of the LSRS. The findings achieved from this research can be used to design an LSRS of required torsional properties which allows the steering to have equal torsional stiffness in both directions. In general, the LSRS enhances driver’s confidence in active steering technology.